Risk factors for osteoporosis and fragility fractures in patients with systemic lupus erythematosus. Issue 1 (19th January 2016) - Carli, L; Tani, C; Spera, V; Vagelli, R; Vagnani, S; Mazzantini, M; Di Munno, O; Mosca, M
Abstract : Osteoporosis (OP) and fragility fractures (FFx) are a known comorbidity in patients with systemic lupus erythematosus (SLE). This work aimed at evaluating (1) the prevalence of OP and FFx in a cohort of SLE and (2) the risk factors associated with both OP and FFx. The following data were collected from clinical charts: age, sex, menopausal status (MP), body mass index, smoking habits, disease duration, daily dose and cumulative glucocorticoids (GCs), type of organ involvement, comorbidities and medications. Data on bone metabolism, calcium and vitamin D supplementation and treatment with bisphosphonates, teriparatide or denosumab were collected, together with bone mineral density (BMD) values (measured by dual-energy X-ray absorptiometry (DXA)) and history of FFx (occurred after the onset of SLE and unrelated to trauma). OP and reduced BMD were defined according to the WHO. 186 patients were included (women 175, men 11; mean age 46.4±13 years, mean disease duration 14.9±9 years). At their last visit, 97 patients (52.2%) had a reduced BMD and 52 (27.9%) had OP. 22 patients (11.8%), all women, had at least one FFx; six patients (27.3%) were pre-menopausal. On univariate analysis, age, cumulative dose of GC, MP, therapy with antiepileptics and chronic renal failure (CRF) were correlated with OP (p<0.03); age, total amount of GC, MP, CRF, anticoagulants (AC) and antiepileptic therapy were correlated with FFx (p<0.05). The multivariate logistic model confirmed a direct association of OP and age, MP and antiepileptic therapy (p≤0.01) and of FFx and age, chronic therapy with AC and antiepileptics (p<0.03). In conclusion, low BMD is frequently observed in SLE, and FFx are observed also in premenopausal patients. Together with traditional risk factors (age, MP and GC), CRF and chronic treatments with AC or antiepileptics seem to be associated with a higher risk profile for OP and FFx occurrence.